Comparative performance of different cropping systems based on pigeonpea (Cajanus cajan) - Yadava, N D; Yadav, D S (The Indian Journal of Agricultural Sciences, 2012)
All experiment was conducted during 1985-86 and 1987–88 under upland condition to study the comparative performance of pigeonpea [Cajanus cajan (L.) Millsp.]-based cropping systems. Pigeonpea–wheat [Triticum aesrivum (L.) emend. Fiori & Paol] gave the highest total biological yield (11.70 tonnes/ha) and grain yield in pigeonpea-yield equivalent (2.84 tonnes/ha), which was significantly higher than that obtained in pigeonpea-ratoon (cutting) and pigeonpea–ratoon (picking) systems. Pigconpea-Â wheat cropping system proved more economical, with a net profit of Rs 10,814/ha than pigeonpea-ratoon (cutting) and pigeonpea-ratoon (picking). However, benefit: cost ratio was highest (1.89) in pigeonpea- ratoon( cutting), followed by pigeonpea-ratoon (picking), and the lowest (1.17) in pigeonpea–wheat system.